Relação entre as emissões de N2O e a expressão dos genes do ciclo do nitrogênio em um solo cultivado com milho sobre resíduo de ervilhaca - Andrade, Nariane de (2022)
Addition legume residues as cover crops may increase soil N2O emissions under no-tillage system. However, when there is water deficit and grass cultivation in succession, the activity of denitrifying microorganisms and emissions may be lower. This study aimed to quantify the N2O emissions from a soil cultivated with maize under no-tillage, covered with different amounts of vetch residues, and under water deficit conditions, and to relate the N2Oemissions with the expression of key genes of denitrifying soil communities. Therefore, a field experiment was set up to cultivate maize on residues of Vicia villosa Roth. at 0, 3, 6, and 9 Mg MS ha-1. During 161 days, the emission of N2O and CO2, mineral N, moisture, temperature, decomposition of residues were quantified. In addition, the levels of C and N in the plants were also analysed. For the dates with the highest N2O emissions, the soil mRNA was extracted and used to study the relative expression of the nirK and nosZ genes. The accumulated emissions of N2O were similar between the treatments with residues of V. villosa (on average 0.645 kg ha-1). The maize plants absorbed N (66, 83, and 103 kg ha-1) proportionally to the amount of residue deposited on the soil surface. As a result, there was a reduction in the availability of soil mineral N, which associated with the water deficit, resulted in low accumulated emissions of N2O. The expression of nirK and nosZ genes by this soil community is lower When the soil N2O emission increases.